Adsorption material, preparation method and application of adsorption material in dechlorination of fluosilicic acid
By using modified ferrocene-loaded adsorption materials on porous graphite, chlorine in fluosilicate is solved, and the chlorine removal efficiency and cost in the prior art is achieved, efficient and economical removal of chlorine is achieved, and the yield and purity of hydrogen fluoride are improved.
Patent Information
- Application Number
- CN202411633071.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, there are problems with the removal efficiency and cost of chlorine in fluosilicate, and the existing methods are difficult to effectively remove chlorine, which affects the yield and purity of hydrogen fluoride.
Using an adsorption material including modified ferrocene and porous graphite, the chlorine element is adsorbed by loading the modified ferrocene on the porous graphite and its good adsorption properties are used.
The adsorbent material can effectively adsorb chlorine in fluosilicate, reduce the content of chlorine, improve the yield and purity of hydrogen fluoride, and the adsorbent can be recycled to reduce production costs.
Smart Images

Figure CN119565570A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an adsorption material, in particular to an adsorption material for chlorine element in the process of preparing hydrogen fluoride from fluosilicic acid and a preparation method thereof. Background Art
[0002] Fluorides are closely related to our lives. Fluorides can be divided into inorganic fluorides and organic fluorides. Among them, inorganic fluorides such as cryolite and hydrofluoric acid are widely used in industries such as electrolytic aluminum and chip manufacturing; while organic fluorides play an important role in the fields of medicine and refrigerants.
[0003] Fluorine is extremely active and can react with almost all elements, so fluorine mainly exists in the form of compounds. In nature, fluorite (CaF2) contains a high proportion of fluorine, and its mining and use costs are relatively low, so it has become the main source of fluorine. However, with the mining and consumption of fluorite ore and increasingly stringent regulatory requirements, the development of new fluorine sources has gradually become a consensus in the fluorine chemical industry.
[0004] Phosphate fertilizer industry mainly uses phosphate rock as raw material. Phosphorus in phosphate rock is usually accompanied by fluorine, silicon, iodine, chlorine, rare earth and other metal elements. When wet-process phosphoric acid is produced from phosphate rock, a large amount of fluorine-containing gas will be produced. After being absorbed and treated by water, these gases will be obtained to obtain 10-18% fluosilicic acid by mass. Under normal circumstances, at least 0.05 tons of pure fluosilicic acid will be produced as a by-product for every ton of wet-process phosphoric acid (pure P2O5). It can be seen that the fluosilicic acid produced as a by-product of phosphate fertilizer contains a large amount of fluorine. If it can be fully utilized, it can alleviate the increasingly tense supply of fluorine.
[0005] In the prior art, the production of fluoride using fluorosilicic acid has been widely studied. For example, CN102275877A discloses a method for producing anhydrous hydrogen fluoride and silicon tetrafluoride using fluorosilicic acid, wherein a fluorosilicic acid solution is reacted with sodium sulfate to obtain sodium fluorosilicate, and sodium fluorosilicate is then mixed with concentrated sulfuric acid to obtain silicon tetrafluoride gas and anhydrous hydrogen fluoride products. Another example is CN116409751A discloses a method and system for producing hydrogen fluoride, which belongs to the process of preparing hydrogen fluoride by the fluorosilicic acid sulfuric acid method. The scheme is to react fluorosilicic acid and the first concentrated sulfuric acid in the main reaction zone to generate silicon tetrafluoride gas and a sulfuric acid solution containing hydrogen fluoride, wherein the silicon tetrafluoride gas is passed into the silicon tetrafluoride generation zone, and the sulfuric acid solution containing hydrogen fluoride is split to form at least two paths for preparing hydrogen fluoride gas. This patent application directly conducts sulfuric acid circulation treatment in parallel in the separation section, and uses sulfuric acid to treat the gas in each section to improve the HF yield and purity.
[0006] However, as mentioned above, phosphate rock is also accompanied by elements such as silicon, iodine, and chlorine. Among them, chlorine has the greatest impact on the sulfuric acid process because the presence of chlorine will reduce the yield of hydrogen fluoride. Therefore, the chlorine in fluosilicic acid needs to be removed.
[0007] There are also reports on the treatment of chlorine in fluorosilicic acid in the prior art.
[0008] For example, CN108455616A and CN108946740A utilize the difference in boiling points between fluorosilicic acid and hydrogen chloride gas, and separate fluorosilicic acid from hydrogen chloride by heating and evaporating fluorosilicic acid and then condensing it. But in fact, since high-concentration fluorosilicic acid is unstable, it will spontaneously decompose at room temperature when the concentration exceeds 60%. The fluorosilicic acid aqueous solution contains about 18-25% fluorosilicic acid and 0.5-2.5% hydrogen chloride, but due to the low concentration of hydrogen chloride, the partial pressure of hydrogen chloride in the gas phase is low, while the partial pressure of water is high, so the actual vacuum distillation process is to concentrate fluorosilicic acid rather than remove hydrogen chloride. Therefore, the efficiency and cost of removing hydrogen chloride from fluorosilicic acid in the schemes disclosed in these two patent applications are issues that need to be considered.
[0009] For example, CN111252770A discloses a method for removing chlorine from fluosilicic acid by electrolysis, using a carbon plate as the cathode and a carbon plate or titanium alloy plate as the substrate with rare metals such as ruthenium or iridium plate plated on the surface as the anode to electrolyze the fluosilicic acid. However, the titanium-based ruthenium-iridium anode used in this scheme has been proven to be intolerant to fluorine and will dissolve and fall off significantly in a short period of time; and the use of carbon plate as the anode is not feasible. According to the C and Cl - The standard oxidation potential of the carbon electrode is 5.8 to 8 V, and the oxidation reaction of the carbon electrode will precede the Cl - The carbon electrode will eventually oxidize rapidly, making the entire electrolysis system unable to operate.
[0010] CN118374827A also discloses a method for electrolytic dechlorination, which improves CN111252770A and overcomes its shortcomings. Specifically, a conductive coating electrode is prepared, which includes a substrate and a conductive coating, wherein the substrate is one of metal titanium, nickel, copper or alloy, and the conductive coating includes an organic solvent, an adhesive and a conductive filler, and the conductive filler includes a main material and an auxiliary material, and the main material is a metal oxide. Although the solution disclosed in this patent application overcomes the problem of short electrode service life, its electrode production process and cost requirements are relatively high, and the electrolysis of dilute fluorosilicic acid also requires a lot of electricity consumption, which brings considerable pressure to enterprises.
[0011] Another example is CN114345106A, which utilizes the difference in absorption rates of hydrogen chloride gas and silicon tetrafluoride gas by water to separate silicon tetrafluoride gas and hydrogen chloride gas. However, the absorption product obtained by this method is still in the production system and is not fundamentally removed.
[0012] CN118183754A discloses a method for removing chlorine by adsorption, which uses hydrogen peroxide to oxidize the chloride ions in fluorosilicic acid into chlorine gas and then uses activated carbon for adsorption, thus overcoming the effect of activated carbon on Cl - Poor adsorption effect. Although the scheme claims that the adsorption of fluorine is small and the concentration of fluorosilicic acid after adsorption does not decrease significantly, in fact, due to the introduction of hydrogen peroxide solution (mass concentration 15-50%), a large amount of water enters the system, which brings greater pressure to the concentration process of fluorosilicic acid. This process is the stage with the highest energy consumption in the fluorosilicic acid acid process, resulting in a significant increase in production costs.
[0013] This shows that the existing technology for dechlorination of fluorosilicic acid still needs further research and improvement. Summary of the invention
[0014] In order to improve the removal effect of chlorine in the fluosilicic acid process and solve the problems existing in the prior art, the present invention provides an adsorption material and a preparation method thereof, as well as an application thereof in fluosilicic acid dechlorination.
[0015] Specifically, a first aspect of the present invention is to provide an adsorption material, which includes modified ferrocene and porous graphite, wherein the modified ferrocene is supported on the porous graphite.
[0016] The modified ferrocene in the present invention is fluoroferrocene, and most preferably is monofluoroferrocene.
[0017] Furthermore, in order to ensure that the adsorption material has a good adsorption effect on the chlorine element, the parameters of the porous graphite and the loading amount of the modified ferrocene can be limited.
[0018] The specific surface area of porous graphite is preferably 300-800 m 2 / g, for example, you can choose 300, 400, 500, 600, 700, 800m 2 / g, and the porosity of the porous graphite is preferably 15-30%, for example, 15, 18, 20, 22, 25, 30%.
[0019] Porous materials are usually characterized by parameters such as specific surface area, porosity, and pore size distribution. In the present invention, the specific surface area and porosity of porous graphite are limited, and the pore size distribution can also be estimated indirectly. Using porous graphite with the above-mentioned specific surface area and porosity, its pores are rich enough, and the pore size is suitable for the deposition of modified ferrocene, providing sufficient time conditions and area conditions for the contact and adsorption of modified ferrocene with chlorine. When using porous graphite materials with higher specific surface area and porosity, its production cost will be higher, and the strength of graphite as a matrix will be lost, which is easy to cause damage to the material and even affect normal production.
[0020] In the present invention, the loading amount of modified ferrocene is determined to have an impact on the adsorption effect. When the loading amount of modified ferrocene is small, for example, less than 0.5%, the adsorption space provided by porous graphite cannot be fully utilized, the absorption amount of chlorine is small, and it needs to be cleaned and replaced frequently. When the loading amount of modified ferrocene is high, the deposition layer on porous graphite is thicker, which will cause part of the modified ferrocene to be unable to be fully absorbed and utilized, and will also block part of the fine pores, affecting production efficiency. Therefore, in combination with the specific parameters of porous graphite, the loading amount of modified ferrocene selected in the present invention, that is, the percentage of its mass to the mass of the adsorbent material, is preferably 1-8%, for example, 1, 2, 4, 4.5, 5, 6, 8%, etc. can be selected.
[0021] The second aspect of the present invention is to provide a method for preparing the above-mentioned adsorption material, specifically, loading the modified ferrocene on the outer surface and / or pore wall of the porous graphite.
[0022] The present invention does not limit the method of loading fluoroferrocene on porous graphite, and any method that can load fluoroferrocene on the outer surface and / or pore wall of porous graphite and form relatively stable attachment can be used, such as deposition method, impregnation method, plating method, etc. Vapor deposition method and impregnation method are preferred because they are low in cost and can load evenly.
[0023] Furthermore, when the vapor deposition method is used, the modified ferrocene gas can be carried by a carrier gas at 110-130°C and deposited on porous graphite for 1-10 hours to obtain a loaded composite material. The modified ferrocene forms vapor in the range of 110-130°C, and is then carried by a carrier gas to the porous graphite for cooling and deposition. By controlling the deposition time, the loading amount of the modified ferrocene can be adjusted.
[0024] Specifically, when performing vapor deposition, firstly, an inert gas is continuously introduced into the deposition equipment to achieve replacement of the gas environment to avoid the occurrence of mixed reactions; then the modified ferrocene is heated to 110-130°C to obtain modified ferrocene gas, at which time the modified ferrocene gas is mixed with the inert gas and passed to the porous graphite under the drive of the inert gas. During the movement of the modified ferrocene gas and the contact with the porous graphite, the temperature gradually decreases and the modified ferrocene gas is deposited on the outer surface of the porous graphite and the inner wall of the pores.
[0025] The present invention does not require inert gas, and commonly used inert gases such as nitrogen, argon, helium, etc. can be used for atmosphere replacement and carrier gas. Considering the production cost, nitrogen is preferred.
[0026] In the present invention, the volume of the modified ferrocene gas, as a ratio of the total volume of the modified ferrocene gas and the inert gas used to carry the modified ferrocene gas for movement, is preferably in the range of 35-80%, for example, 35, 40, 50, 55, 60, 70, 80%, etc. If it is lower than this range, the content of the modified ferrocene gas is low, resulting in low deposition efficiency; if it is higher than this range, more modified ferrocene is carried away by the carrier gas before being deposited, resulting in waste.
[0027] In addition, it should be pointed out that in the present invention, a blower, a gas nozzle, an exhaust fan and other equipment can be added to the gas input or output end of the deposition equipment, or other known means can be used to increase and control the gas flow rate, thereby promoting more gas to pass through the pores of the porous graphite and form a deposition layer on the pore wall.
[0028] Furthermore, when the impregnation method is used, fluoroferrocene is dissolved in a solvent to obtain an impregnation solution, and then the porous graphite is immersed in the impregnation solution for 5-48 hours, and the impregnation solution fully penetrates into the pores of the porous graphite and adheres to its surface. After the impregnation is completed, the porous graphite with the modified ferrocene attached is washed with deionized water several times and then dried.
[0029] The present invention does not specifically require the solvent, and any solvent that can dissolve the modified ferrocene and does not react with the porous graphite or strongly adsorb can be used, preferably benzene or toluene. The present invention does not specifically limit the drying method, and infrared drying, hot air drying, drying oven drying and the like are all possible, but the drying temperature should not be too high, and 60-80°C is the best.
[0030] In order to enhance the impregnation effect, nitrogen bubbling or slow stirring can be adopted during the impregnation process.
[0031] It should be pointed out that the present invention does not make specific requirements for the preparation method of the porous graphite of the support matrix, and any method that can obtain porous graphite with the required specific surface area and porosity can be adopted. For example, porous graphite can be obtained by adding a foaming material to graphite as disclosed in CN117712299A, or by a method of granulating graphite powder as disclosed in US20120211212A1, or by a 3D printing method as disclosed in CN117602949A.
[0032] It should also be noted that the adsorbent material is preferably prepared by vapor deposition. When prepared by vapor deposition, the modified ferrocene raw material does not directly contact the porous graphite, but is deposited by forming a gas, which effectively avoids the influence of impurities in the modified ferrocene, and impurities are difficult to form gaseous deposits in the porous graphite. Therefore, the purity of the modified ferrocene as a raw material can be appropriately reduced, further reducing production costs.
[0033] The third aspect of the present invention is to provide the application of the above-mentioned adsorption material or the adsorption material obtained according to the above-mentioned method. Specifically, the adsorption material is used for adsorption of chlorine in fluosilicic acid and / or adsorption of chlorine in hydrogen fluoride.
[0034] The adsorption material disclosed in the present invention has a good adsorption effect on the chlorine element, can effectively absorb the impurity chlorine in fluosilicic acid, and reduce the chlorine element content.
[0035] Furthermore, the adsorption material disclosed in the present invention is particularly suitable for adsorbing chlorine in the process of preparing hydrogen fluoride from fluosilicic acid. Specifically, the chlorine in the fluosilicic acid raw material can be adsorbed to reduce the chlorine content entering the anhydrous hydrogen fluoride production system, thereby reducing the content of hydrogen chloride in the subsequently produced hydrogen fluoride.
[0036] Furthermore, after the adsorption material disclosed in the present invention adsorbs a certain amount of chloride ions, the chloride ions can be removed so that the adsorbent is regenerated, and the adsorption material can be recycled for multiple times, thereby reducing production costs. For example, after the adsorption reaches a saturated state, the adsorption material adsorbed with chlorine can be treated with ultrasonic vibration in a weak alkaline eluent to remove the chlorine; and when the adsorption material is recycled for multiple times, a supercritical liquid, such as supercritical carbon dioxide, can be used to contact the adsorption material with the supercritical liquid, adjust the temperature and pressure, and utilize the good solubility of the supercritical liquid in chloride ions to achieve extraction of chlorine and remove chlorine.
[0037] The adsorption material disclosed in the present invention selects porous graphite as the loading matrix. Firstly, the good thermal stability and chemical stability of graphite are utilized, and the graphite can be stably used in a high temperature, strong acid and strong corrosive environment; secondly, the abundant pores of the porous graphite are utilized to provide a broad attachment space for the active adsorption material fluoroferrocene.
[0038] The adsorption material disclosed in the present invention is loaded with fluorinated ferrocene, which utilizes the iron metal element at the center of ferrocene. - It coordinates with the central ferrous ion, thereby achieving the adsorption and removal of chlorine. In addition, since the ionization energy of fluorine ions is significantly greater than that of chloride ions, the modified ferrocene will preferentially adsorb chlorine, while absorbing less fluorine, which means that it has little effect on the concentration of fluorosilicic acid and hydrogen fluoride.
[0039] The adsorption material disclosed in the present invention has a simple preparation process, the raw materials are cheap and easily available, and the harm to human body and environment is small. Experiments have proved that the adsorption material disclosed in the present invention can be used to treat fluorosilicic acid to effectively adsorb the chloride ions therein, and the adsorption material can be recycled after elution and regeneration. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 The graph is a graph showing the change in chloride ion concentration over time in Examples 9-10 and Comparative Examples 5-7. DETAILED DESCRIPTION
[0041] The fluoroferrocene used in the following examples are all monofluoroferrocene.
[0042] Example 1
[0043] An adsorption material, comprising a porous graphite support substrate and fluoroferrocene supported on the surface and pore walls of the porous graphite, wherein the specific surface area of the porous graphite is 616m 2 / g, the porosity is 24%, and the loaded fluoroferrocene accounts for 6.3% of the total mass of the adsorption material.
[0044] Example 2
[0045] An adsorption material, comprising a supporting matrix porous graphite and fluoroferrocene supported thereon, wherein the specific surface area of the porous graphite is 318 m 2 / g, the porosity is 17%, and the loaded fluoroferrocene accounts for 1.8% of the total mass of the adsorption material.
[0046] Example 3
[0047] An adsorption material, comprising a loaded matrix porous graphite and loaded fluoroferrocene, wherein the specific surface area of the porous graphite is 760m 2 / g, the porosity is 30%, and the loaded fluoroferrocene accounts for 7.7% of the total mass of the adsorption material.
[0048] Comparative Example 1
[0049] An adsorption material, which is different from Example 1 in that the loaded fluoroferrocene accounts for 0.4% of the total mass of the adsorption material.
[0050] Comparative Example 2
[0051] An adsorption material, comprising a loaded matrix porous graphite and loaded fluoroferrocene, wherein the specific surface area of the porous graphite is 180 m 2 / g, the porosity is 10%, and the loaded fluoroferrocene accounts for 1.7% of the total mass of the adsorption material.
[0052] Example 4
[0053] The method for preparing the adsorbent material in Example 1 comprises the following steps:
[0054] S1, referring to the scheme disclosed in CN117712299A, porous graphite is prepared using mesophase asphalt as raw material, and a piece of porous graphite with abundant pores and uniform pore size is taken, and its mass is weighed as m1;
[0055] S2, placing the porous graphite in a ceramic boat, and placing it in the middle of a deposition furnace, and placing the modified ferrocene in the deposition furnace and at an upwind position of the porous graphite;
[0056] S3, nitrogen is continuously introduced into the deposition furnace for 30 minutes to perform gas replacement. After the replacement is completed, nitrogen is continuously introduced to heat the fluoroferrocene slowly to 120° C. to obtain vapor. The fluoroferrocene vapor flows toward the porous graphite driven by the nitrogen. At this time, the volume ratio of nitrogen to fluoroferrocene gas in the deposition furnace is controlled to be approximately 1:2;
[0057] S4, continue deposition for 4 h, stop heating and continue to introduce nitrogen until the deposition furnace returns to room temperature, take out the porous graphite, wash it with flowing deionized water for 5 min, and dry it with 70°C hot air to constant weight to obtain the adsorption material, and weigh the mass m2.
[0058] In this embodiment, m1 and m2 are 12.70 g and 13.55 g respectively, that is, 0.85 g of fluoroferrocene is loaded, and the loading rate is 6.27%.
[0059] The parameters of the porous graphite obtained by S1 were measured by BET method and mercury intrusion method, and the specific surface area was 616.2 m 2 / g, and the porosity is 24.37%.
[0060] Example 5
[0061] A method for preparing an adsorbent material comprises the following steps:
[0062] S1, according to the scheme disclosed in US20120211212A1, porous graphite is prepared, and its specific surface area is 380m 2 / g, porosity is 18.2%,
[0063] S2, placing the porous graphite in a ceramic boat, placing it in the middle of a deposition furnace, taking fluoroferrocene and placing it in the deposition furnace and at the upwind position of the porous graphite;
[0064] S3, continuously introducing argon gas into the deposition furnace for 50 minutes to replace the gas, and continuing to introduce argon gas after the replacement is completed, heating the fluoroferrocene slowly to 110° C. to obtain vapor, and the fluoroferrocene vapor flows toward the porous graphite under the drive of nitrogen gas, and at this time, the volume ratio of nitrogen gas to fluoroferrocene gas in the deposition furnace is controlled to be approximately 1:1;
[0065] S4, continue deposition for 1.5 h, stop heating and continue to introduce nitrogen until the deposition furnace returns to room temperature, take out the porous graphite, wash it with flowing deionized water for 5 min, and dry it with 70°C hot air to constant weight to obtain an adsorption material with a loading rate of 2.7%.
[0066] Example 6
[0067] The method for preparing the adsorbent material of Example 6 is different from that of Example 5 in that the deposition in step S4 is performed for 10 hours, and the loading rate of the adsorbent material obtained is 5.1%.
[0068] Example 7
[0069] The method for preparing the adsorbent material in Example 2 comprises the following steps:
[0070] S1, dissolve 5 g of fluoroferrocene in 80 mL of toluene and stir evenly to obtain an impregnation solution;
[0071] S2, take 10g of porous graphite and measure its specific surface area to be 318m 2 / g, with a porosity of 17%, the porous graphite is placed in an impregnation solution, and argon gas is continuously blown in to disturb the liquid phase system;
[0072] S3, after immersion for 10 h, the porous graphite was taken out, washed with deionized water, and then dried at low temperature under infrared light to obtain an adsorption material with a weight of 10.18 g, i.e., a loading rate of 1.8%.
[0073] Example 8
[0074] A method for preparing an adsorbent material comprises the following steps:
[0075] S1, dissolve 3 g of fluoroferrocene in 70 mL of benzene and stir evenly to obtain an impregnation solution;
[0076] S2, taking 5 g of porous graphite of the same number as used in Example 7 and placing it in the impregnation solution, and continuously stirring at a rate of 10 r / min with a stirring rod;
[0077] S3, after immersion for 48 h, the porous graphite was taken out, washed with deionized water, and then dried with hot air to obtain an adsorbent material with a loading rate of 3.3%.
[0078] Comparative Example 3
[0079] A method for preparing an adsorbent material, which is different from Example 4 in that the deposition time is 18 hours and the adsorbent material loading rate obtained is 10.3%.
[0080] It was observed that the outer surface of the porous graphite was covered with a thick layer of loose orange fluoroferrocene. Compared with the undeposited porous graphite, the visible pores were significantly reduced, and some pores were severely blocked by yellow substances.
[0081] Comparative Example 4
[0082] A method for preparing an adsorbent material, which is different from Example 6 in that in step S3, the volume ratio of nitrogen to fluoroferrocene gas is controlled at approximately 3:1, that is, the volume content of fluoroferrocene is about 25%, and the loading rate of the final adsorbent material is 2.5%.
[0083] By comparing Example 6 with Comparative Example 4, it can be found that when there is too much nitrogen in the carrier gas, the deposition efficiency of fluoroferrocene will be affected, and the loading rate will be lower within the same deposition time. Although extending the deposition time can increase the loading rate to a certain extent, it will put pressure on production efficiency and cost.
[0084] The adsorption materials in the above embodiments or comparative examples are used to adsorb and remove chlorine from the fluosilicic acid solution. The fluosilicic acid used is the byproduct fluosilicic acid produced by a phosphate fertilizer plant, wherein the fluosilicic acid mass content is 18.2%, the chloride ion mass content is 1.4%, and it also contains impurities such as iodine, arsenic, silicon, and calcium.
[0085] Example 9
[0086] Take 13.55 g of the adsorbent material in Example 1, place it in 50 mL of fluorosilicic acid solution, take out a small amount of solution at regular intervals, and use silver nitrate to accurately titrate the chloride ion concentration in the solution to obtain the chloride ion content in the solution as follows: Figure 1 shown.
[0087] Comparative Example 5
[0088] Take 13.55 g of the adsorbent material in Comparative Example 1, and measure the chloride ion concentration in the solution at different times in the same manner as in Example 9. Figure 1 shown.
[0089] Comparative Example 6
[0090] Take 13.55 g of the adsorbent material in Comparative Example 3, and measure the chloride ion concentration in the solution at different times in the same manner as in Example 9. Figure 1 shown.
[0091] It can be seen from Example 9 and Comparative Example 5 that under the same conditions of porous graphite, sufficient fluoroferrocene is loaded, the rate of adsorption in the early stage is faster, and the concentration in the final solution is strongly related to the amount of adsorbent material. When the adsorbent material is less and reaches the adsorption equilibrium state, no further adsorption can be achieved. For example, in Comparative Example 5, the concentration of chloride ions is still around 0.6%, which does not meet the preparation requirements of anhydrous hydrogen fluoride, resulting in more hydrogen chloride mixed in the obtained anhydrous hydrogen fluoride. According to calculations and experimental verification, a fluoroferrocene loading of more than 1% can achieve sufficient adsorption of chlorine in fluorosilicic acid.
[0092] Comparing the adsorption data of Example 9 and Comparative Example 6, when the loading amount is too high, the initial adsorption efficiency will be affected, and the final adsorption amount will also have some adverse effects. This is because when the loading amount is too high, multi-layer accumulation of fluoroferrocene will appear in the porous graphite and block the pores, affecting the contact between the active substances of the adsorption material and fluorosilicic acid.
[0093] Example 10
[0094] Take 10.18 g of the adsorbent material in Example 2, place it in 50 mL of fluorosilicic acid solution, take out a small amount of solution at regular intervals, and use silver nitrate to accurately titrate the chloride ion concentration in the solution to obtain the chloride ion content in the solution as follows: Figure 1 shown.
[0095] Comparative Example 7
[0096] 10.18 g of the adsorption material in Comparative Example 2 was taken, and the adsorption data at different times were measured according to the method of Example 10.
[0097] According to Example 10 and Comparative Example 7, it can be found that when the loading amount is substantially the same, when the specific surface area and porosity of the porous graphite are small, the adsorption effect has a significant difference. This is because the surface and pores of the porous graphite provide space for the combination of modified ferrocene. When the specific surface area and porosity are small, it means that there is less space for the modified ferrocene to attach, and the newly deposited modified ferrocene can only be deposited on the surface of the old modified ferrocene. The internal modified ferrocene is difficult to play an adsorption role, resulting in a decrease in the initial adsorption rate and the final adsorption amount.
Claims
1. An adsorption material, characterized in that: The adsorption material comprises modified ferrocene and porous graphite, the modified ferrocene is loaded on the porous graphite, and the modified ferrocene is fluorinated ferrocene.
2. The adsorption material according to claim 1, characterized in that The specific surface area of the porous graphite is 300-800m 2 / g, the porosity is 15-30%, and the mass of the modified ferrocene is 1-8% of the mass of the adsorption material.
3. The method for preparing the adsorbent material according to claim 1, characterized in that: A porous graphite carrier is prepared, and the modified ferrocene is loaded on the outer surface and / or pore wall of the porous graphite.
4. The preparation method according to claim 3, characterized in that: The loading method includes a vapor deposition method and an impregnation method.
5. The preparation method according to claim 4, characterized in that: The vapor deposition method is carried out under the condition of a carrier gas and at a temperature of 110-130° C. for 1-10 hours.
6. The preparation method according to claim 5, characterized in that: After continuously introducing inert gas into the deposition equipment to complete atmosphere replacement, the modified ferrocene is heated to 110-130° C., and the obtained modified ferrocene gas is driven by the inert gas to flow into the porous graphite, wherein the volume ratio of the modified ferrocene gas to the gas is 35-80%.
7. The preparation method according to claim 4, characterized in that: The impregnation method is to dissolve the modified ferrocene in a solvent to obtain an impregnation solution, then immerse the porous graphite in the impregnation solution for 5-48 hours, wash and dry.
8. The preparation method according to claim 7, characterized in that: The solvent is benzene or toluene, and nitrogen is blown into the immersion process or the immersion process is slowly stirred.
9. Use of the adsorbent material according to any one of claims 1 or 2, or the adsorbent material obtained by the preparation method according to any one of claims 3 to 8, characterized in that: The adsorption material is used for adsorbing chlorine element in fluosilicic acid.
10. The use according to claim 9, characterized in that: The adsorption material is used for adsorbing chlorine in the process of preparing hydrogen fluoride from fluosilicic acid.
Citation Information
Patent Citations
A method for producing anhydrous hydrogen fluoride and silicon tetrafluoride using fluorosilicic acid
CN102275877A
Chlorine removing method and device of fluosilicic acid
CN108455616A
Dechlorination method and device
CN108946740A
Method for removing chlorine from fluosilicic acid
CN111252770A
Method and system for removing chlorine element in production process of anhydrous hydrogen fluoride
CN114345106A